Ending War Crimes, Chasing the War Criminals. - Power, Jonathan (Raoul Wallenberg Institute human rights library., 2017)
Until the publication of this book there has been no book on this important issue of our age. There are books on genocide, Cambodia, the International Court for Crimes Against Humanity, Henry Kissinger, etc. but no overview of the whole subject and its history. It begins with an analysis of the characters of Adolf Eichmann and Heinrich Himmler, the two men in charge of the Final Solution. Neither men saw what they did as wrong. Himmler grew up in a sober, loving family yet turned into a monster. The book moves on to look at the role played by some of Africa's war criminals and how they came for trial at the ICC. The Western world also has its alleged war criminals including the self-confessed war criminal Robert McNamara who led the war in Vietnam on behalf of Presidents Kennedy and Johnson. There are portraits of Henry Kissinger, George W. Bush, Tony Blair, General Pinochet and General Sharon, all of whom many consider to be war criminals. Guatemala, said Amnesty International, was a country with no political prisoners, only political killings. The author was the journalist responsible for proving that the president was personally directing the death squads which decimated Indian villages and opposition figures. The book also tracks the wars, the genocide and, later, the ICC trials in Cambodia and ex-Yugoslavia. In a final chapter, it asks the question: Can human rights be pursued by making war? The author has travelled to and reported from nearly all the countries he writes about.